Aerogel thermal insulation putty paste and preparation method thereof

By optimizing the raw material formula of aerogel insulation putty paste, combining high Tg value emulsion and modified aerogel paste, the problems of mechanical strength and bonding effect of putty paste are solved, and the efficient insulation and good bonding of putty paste are achieved. performance.

CN116218274BActive Publication Date: 2025-02-07SUZHOU AISHI HIGH-TECH MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310228159.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-02-07
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing aerogel insulation putty paste has problems such as decreased mechanical strength, reduced bonding effect, and poor dispersion during use, resulting in unsatisfactory insulation effect.

Method used

By optimizing the raw material formula, including the use of high Tg value emulsions and modified aerogel paste, adding fillers and adhesion promoters, combining leveling agents, defoaming agents, wetting and dispersing agents, and bactericides, to form excellent insulation with excellent insulation and bonding properties putty paste.

Benefits of technology

The putty paste has achieved high mechanical strength, good bonding effect and excellent thermal insulation performance, avoiding the problem of improving the water absorption and decreasing bonding strength of putty paste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application provides an aerogel thermal insulation putty paste, the raw materials of which include: by weight, 13-50 parts of emulsion, 30-70 parts of aerogel paste, 5-30 parts of filler, 0.1-2 parts of leveling agent, 0.1-3 parts of adhesion promoter, 0.1-1 parts of defoaming agent, 0.1-1 parts of bactericide, 0.1-1 parts of wetting dispersant, and 5-20 parts of water; the present application uses a high-density aerogel paste, and the prepared putty paste has excellent thermal insulation performance and flame retardant performance; at the same time, the mechanical strength of the putty paste is enhanced by using an emulsion with a high Tg value, and the flexibility of the cross-linking system of the putty paste is coordinated by compounding different emulsions to avoid cracking or powdering of the putty paste after curing, and the prepared putty paste has excellent bonding strength, fire resistance, hydrophobicity and construction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building thermal insulation materials, and in particular to an aerogel thermal insulation putty paste and a preparation method thereof. Background Art

[0002] Energy-saving renovation of buildings is a huge project: (1) Due to the complexity of construction and low safety factor, it is no longer suitable to re-hang insulation materials such as polystyrene boards and rock wool on exterior walls; (2) Insulation boards will significantly reduce the existing space in the room, and the fire rating problem also limits the application of insulation boards in interior wall renovation. Therefore, low thermal conductivity insulation coating products are an obvious trend in future energy-saving renovations and have a very obvious effect.

[0003] The thermal insulation coating products currently on the market mainly include putty paste, paint, and inorganic thermal insulation mortar; among them, putty paste is easy to construct and environmentally friendly, and has received increasing attention from the building materials and home improvement industry. However, most putty pastes use glass beads as thermal insulation fillers, and the thermal insulation effect and fire resistance are still insufficient. In addition, the water resistance, weather resistance, construction performance, and mechanical strength of putty paste also need to be further improved to cope with use in indoor and outdoor environments.

[0004] Aerogel materials have been used in the field of thermal insulation due to their unique advantages. For example, Chinese patent CN108529990B discloses a building exterior wall thermal insulation putty and its preparation method, the formula of which includes: inorganic adhesive material, inorganic expansion foaming material, composite magnesium aluminum silicate, modified aerogel material, phase change energy storage material, hydroxyethyl cellulose, ceramic fiber, wetting dispersant and silicon-modified polymer powder. The thermal insulation performance of the putty is improved by the combined effect of modified aerogel and modified polymer powder. Chinese patent CN103911030A discloses a method for preparing aerogel thermal insulation coating, the formula components include aerogel, film-forming resin, functional material, defoamer, wetting agent, leveling agent, dispersant, the prepared coating has a wide temperature range and good thermal insulation effect.

[0005] However, there are still many problems in the use of aerogel. For example, its addition will reduce the mechanical strength of the putty paste, especially the compressive strength of the putty paste will decrease significantly after it is immersed in water; it will also easily reduce the bonding effect of the putty paste and easily cause the latter to fall off the building substrate; in addition, its dispersibility is poor, resulting in large differences in the performance of various parts of the product and the thermal insulation effect cannot reach the ideal value, etc. Summary of the invention

[0006] In order to solve the above technical problems, the present invention first provides an aerogel thermal insulation putty paste.

[0007] Furthermore, the raw materials of the thermal insulation putty paste include: by weight, 13-50 parts of emulsion, 30-70 parts of aerogel paste, 5-30 parts of filler, 0.1-2 parts of leveling agent, 0.1-3 parts of adhesion promoter, 0.1-1 parts of defoaming agent, 0.1-1 parts of bactericide, 0.1-1 parts of wetting dispersant, and 5-20 parts of water.

[0008] In the present application, the emulsion constitutes a connecting bridge within the putty paste system and gives the putty paste structural strength, weather resistance and bonding strength; the aerogel is selected to increase the thermal insulation and fire resistance of the putty paste and increase the pore structure; the filler further increases the strength and air tightness of the putty paste and improves the fineness of the putty paste when scraped; the adhesion promoter helps solve the problem of decreased bonding strength of the putty paste when using aerogel and filler; the leveling agent, defoaming agent and wetting dispersant increase the dispersion uniformity and construction performance of the putty.

[0009] Preferably, the raw materials of the thermal insulation putty paste include: by weight, 15-35 parts of emulsion, 40-60 parts of aerogel paste, 5-15 parts of filler, 0.1-1 parts of leveling agent, 0.1-2 parts of adhesion promoter, 0.1-0.5 parts of defoaming agent, 0.1-0.8 parts of bactericide, 0.1-0.8 parts of wetting dispersant, and 5-12 parts of water.

[0010] The use of aerogel will cause the problem of decreased mechanical strength of putty paste. If the strength is increased only by increasing the amount of filler, the strength improvement is not obvious, and there will be problems such as decreased bonding strength, powdering or cracking of putty; therefore, this application is studied from the aspect of emulsion. The glass transition temperature can be used as the shaping transformation temperature of amorphous objects after emulsion dispersion film cross-linking, which is an important process parameter; the molecular chains of the emulsion contact, entangle, and connect with each other in the system to form a network structure, giving the organic-inorganic system bridging structure a certain mechanical strength. When the system is subjected to external forces, this continuous structure can effectively absorb and transfer energy, inhibiting the formation and expansion of cracks; when the glass transition temperature of the emulsion is higher, the free volume of the emulsion molecules under normal conditions is reduced, and the rigidity of the formed bridging structure is stronger, but when the glass transition temperature is too high, the putty will become brittle and powdery.

[0011] Furthermore, the emulsion includes but is not limited to at least one of pure acrylic emulsion, styrene acrylic emulsion, styrene butadiene emulsion, silicone acrylic emulsion, epoxy resin emulsion, and polyvinyl acetate emulsion.

[0012] Preferably, the emulsion comprises styrene acrylic emulsion and polyvinyl acetate emulsion.

[0013] Furthermore, the Tg value of the styrene acrylic emulsion is 20-45°C, and the Tg value of the polyvinyl acetate emulsion is 30-50°C.

[0014] In a preferred embodiment, the emulsion further comprises polyvinyl acetate-ethylene emulsion. Although increasing the glass transition temperature of the emulsion can improve the mechanical strength of the putty paste, the putty paste is too rigid and there is a risk of stress cracking. Therefore, polyvinyl acetate-ethylene emulsion with a low Tg value is added in the present application, and the rigidity and flexibility of the system are adjusted to achieve an optimal balance by introducing soft molecular segments.

[0015] Furthermore, the Tg value of the polyvinyl acetate-ethylene emulsion is -5 to 10°C.

[0016] Furthermore, the weight ratio of the styrene acrylic emulsion, the polyvinyl acetate emulsion and the polyvinyl acetate-ethylene emulsion is 1:(0.5-1):(0.2-1).

[0017] Furthermore, the composition of the aerogel paste is as follows: based on the total weight being 100%, aerogel powder 10-15%, active agent 0.5-6%, and water as the balance.

[0018] Furthermore, the aerogel powder includes at least one of silica aerogel, titania aerogel, alumina aerogel and carbon aerogel; preferably silica aerogel.

[0019] Prefabricating aerogel powder into aerogel paste can solve the problem that aerogel powder is easy to blow away and difficult to disperse, avoid health problems for production personnel, and at the same time, the paste is more excellent in transportation and production efficiency.

[0020] Furthermore, the active agent is selected from at least one of polyoxypropylene glycol ether, ethylene glycol monostearate, polyoxypropylene stearate, polyoxyethylene dioleate, tetraethylene glycol monooleate, polyoxypropylene mannitol dioleate, polyoxyethylene oxypropylene oleate, polyoxyethylene lanolin alcohol ether, and polyoxyethylene fatty acid.

[0021] In a preferred embodiment, the active agent is ethylene glycol monostearate and polyoxyethylene dioleate, and the weight ratio of the two is 1: (1-3). There are a large number of silanol groups on the surface of the silica aerogel powder. When it comes into contact with water, it easily absorbs moisture to cause the pore structure of the aerogel to collapse or pulverize, reducing the thermal insulation effect of the aerogel; the present application uses the -OH component in the structure of ethylene glycol monostearate and polyoxyethylene dioleate to form a bond with the silanol group, and its molecular chain modifies and wraps the silica aerogel, increases the hydrophobicity of the aerogel surface, and maintains its structure and thermal insulation performance. In addition, the surface-modified molecular chain can also interact with the emulsion molecular chain in the system to increase the dispersion and stability of the aerogel in the system. For polyoxyethylene dioleate, the double bonds on its molecular chain can also enhance the bonding performance of the prepared putty paste and the substrate through conjugation.

[0022] Furthermore, the preparation method of the aerogel paste is: aerogel powder, active agent and water are mixed and then stirred at high speed; the stirring speed is 1000-2000 revolutions.

[0023] Furthermore, auxiliary agents such as defoamers, foam stabilizers, and bactericides may be added to the aerogel paste according to actual needs, and the present invention does not make strict regulations on this.

[0024] Furthermore, the aerogel powder has a particle size of 0.3 nm-100 μm, a density of 0.05-1.0 g / mL, and a specific surface area of ​​300-1500 m 2 / g, thermal conductivity is 0.01-0.05W / m·k.

[0025] Preferably, the aerogel has a particle size of 0.5 nm to 500 nm, a density of 0.05 to 0.6 g / mL, and a specific surface area of ​​600 to 1000 m 2 / g, thermal conductivity is 0.015-0.04W / m·k.

[0026] Furthermore, the filler includes at least one of calcium carbonate, ceramic powder, talcum powder, mica powder, quartz powder, glass microbeads, and reinforcing fibers.

[0027] Furthermore, the filler includes calcium carbonate and / or glass microspheres.

[0028] In one embodiment, the calcium carbonate particles have an average diameter of 20-800 nm, preferably 50-200 nm.

[0029] Furthermore, the calcium carbonate is modified calcium carbonate; the modifier used for the modified calcium carbonate is an organic silane substance, selected from at least one of vinyl triethoxysilane, 3-(methacryloyloxy)propyl trimethoxysilane, 3-aminopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane and γ-mercaptopropyl trimethoxysilane. The modification treatment can increase the dispersibility of calcium carbonate and the rheological properties of the putty paste, and can also improve the smooth feel of the putty when scraping. Most importantly, the polar groups in the modifier will produce intermolecular effects with the functional groups in the system or the wall base material, which not only improves the cohesion of the putty paste, but also enhances the bonding strength to the base; however, when too much modifier is added, the cohesion is too strong, the putty is too hard and easy to crack, and the water absorption of the putty paste will also increase.

[0030] In a preferred embodiment, the modifier is γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane.

[0031] Furthermore, the modification method of calcium carbonate is as follows: calcium carbonate is placed in deionized water to form a 5-10wt% suspension, ultrasonically dispersed and then heated to 70-90°C, an ethanol solution containing 4-8wt% of a modifier is added while stirring, the reaction is carried out at a constant temperature and stirred for 1-4h, then filtered and dried to obtain modified calcium carbonate.

[0032] Furthermore, the adhesion promoter is selected from at least one of silicones, phosphates, resins and the like.

[0033] Furthermore, the organosilicon includes but is not limited to at least one of mercaptoalkoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

[0034] Furthermore, the phosphates include but are not limited to at least one of polyepoxy phosphate, 2-hydroxyethyl methacrylate phosphate, and methacryloyloxyethyl phosphate.

[0035] Furthermore, the resins include but are not limited to at least one of epoxy acrylate and amino acrylate.

[0036] Preferably, the adhesion promoter is an organosilicon. The silicon-oxygen bond in the structure of the organosilicon compound forms a silanol group after hydrolysis, which forms an adhesion effect with inorganic substances, and the organic molecular chain at the other end can be interconnected with the organic components in the system; due to this unique characteristic, the addition of organosilicon compounds can promote the adhesion between the organic-inorganic composite system and the inorganic substrate; although the silicon-oxygen bond with a directional arrangement structure can also enhance the mechanical strength of the putty system, this enhancement effect is more obvious when the organosilicon substance has a ring structure.

[0037] In a preferred embodiment, the adhesion promoter is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

[0038] Furthermore, the present application does not make strict regulations on the leveling agent, defoaming agent, bactericide, and wetting and dispersing agent, which can be selected and adjusted according to actual needs.

[0039] Furthermore, the leveling agent is selected from polyacrylates or silicones; preferably silicones, and at least one of BYK302, BYK331, and DC-57 can be selected.

[0040] Furthermore, the defoaming agent is selected from at least one of alcohol esters, acid esters, polyethers, silicones, and mineral oils; and can be selected from at least one of BYK016, BYK021, BYK024, BYK037, BYK141, BYK077, BYK065, TEGO Airex901W, TEGO Airex 902W, and TEGO Foamex 810.

[0041] Furthermore, the wetting and dispersing agent is selected from at least one of fatty acids, fatty amides, polyphosphates, paraffin, and small molecule waxes; preferably paraffin; paraffin, as a phase change energy storage material, can adjust phase changes through changes in indoor and outdoor temperatures to maintain the ambient temperature at an appropriate level, and can work together with aerogel, but its dosage needs to be reasonably controlled.

[0042] Furthermore, the fungicide includes at least one of 5-chloro-2-methyl-4-isothiazoline-3-one, 2-methyl-4-isothiazoline-3-one, and 1,2-benzisothiazolin-3-one.

[0043] Furthermore, the present application also provides a method for preparing the thermal insulation putty paste:

[0044] S1. Mix water, aerogel paste, filler, leveling agent, adhesion promoter, defoamer and wetting dispersant and stir at high speed;

[0045] S2. Add the emulsion and the fungicide into S1 and mix and stir to obtain the thermal insulation putty paste.

[0046] Furthermore, the thermal insulation putty paste is used for building exterior walls or building interior walls.

[0047] Beneficial Effects

[0048] 1. This application uses a high-density aerogel paste, and the prepared putty paste has excellent thermal insulation and flame retardant properties (Grade A); at the same time, a high Tg value emulsion is used to enhance the mechanical strength of the putty paste, and by compounding different emulsions, the flexibility of the cross-linking system of the putty paste is coordinated to avoid cracking or powdering of the putty paste after curing;

[0049] 2. The present application modifies the aerogel powder to improve the dispersibility and stability of the aerogel powder in the organic-inorganic system, further enhance the thermal insulation effect, and improve the problem of decreased mechanical strength and bonding strength caused by adding aerogel powder by optimizing the type of modifier, and also reduce the water absorption of putty paste;

[0050] 3. The present application modifies nano calcium carbonate and optimizes the adhesion promoter, so that the putty paste has excellent bonding properties and improves the construction performance of the putty paste, making it smooth and slippery when scraped. DETAILED DESCRIPTION

[0051] Example

[0052] Example 1

[0053] The present embodiment provides an aerogel thermal insulation putty paste, and the raw materials for preparation include: by weight, 30 parts of emulsion, 50 parts of aerogel paste, 9 parts of filler, 0.2 parts of leveling agent, 0.2 parts of adhesion promoter, 0.3 parts of defoamer, 0.5 parts of bactericide, 0.5 parts of wetting dispersant, and 9.3 parts of water;

[0054] The emulsion is a combination of styrene acrylic emulsion (Tg value is 28°C, Shanghai Zhenzhou Chemical Coatings Co., Ltd. KB-68), polyvinyl acetate emulsion (Tg value is about 42°C, brand name Vinamul 8482) and polyvinyl acetate-ethylene emulsion (Tg value is -3°C, Beijing Ruishengte Building Materials Co., Ltd., model: 707), with a weight ratio of 1:0.7:0.5; the filler is modified calcium carbonate, and the average particle diameter is 120nm; the leveling agent is BYK302; the adhesion promoter is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the defoamer is TEGO Airex901W, the bactericide is 1,2-benzisothiazolin-3-one, and the wetting and dispersing agent is paraffin;

[0055] The preparation method of the aerogel paste is as follows: based on the total weight of 100%, 13% of silica aerogel powder, 4% of active agent and the balance of water are mixed and then stirred and dispersed at 1500r / min; wherein the active agent is ethylene glycol monostearate and polyoxyethylene dioleate, and the weight ratio of the two is 1:2; the particle size of the aerogel powder is 50nm, the density is 0.3g / mL, and the specific surface area is 800m 2 / g, thermal conductivity is 0.01W / (m·k);

[0056] The preparation method of the modified calcium carbonate is as follows: calcium carbonate is placed in deionized water to form an 8wt% suspension, ultrasonically dispersed and then heated to 85°C, an ethanol solution containing 5wt% of γ-mercaptopropyltriethoxysilane (modifier) ​​is added while stirring, the mixture is stirred at a constant temperature for 2h, then filtered and dried to obtain the modified calcium carbonate.

[0057] The preparation method of thermal insulation putty paste is:

[0058] S1. Mix water, aerogel paste, filler, leveling agent, adhesion promoter, defoamer and wetting dispersant in proportion and stir and disperse at a speed of 1200 r / min for 10 min;

[0059] S2. Add the emulsion and the fungicide to the mixture obtained in S1, mix, and stir and disperse at a speed of 2000 r / min for 30 minutes to obtain a thermal insulation putty paste.

[0060] Example 2

[0061] The present embodiment provides an aerogel thermal insulation putty paste, and the raw materials for preparation include: by weight, 35 parts of emulsion, 60 parts of aerogel paste, 10 parts of filler, 1 part of leveling agent, 2 parts of adhesion promoter, 0.5 parts of defoamer, 0.8 parts of bactericide, 0.8 parts of wetting dispersant, and 12 parts of water;

[0062] The emulsion is a combination of styrene acrylic emulsion (Tg value is 24°C, Suzhou Xuming Cibo Chemical New Materials Co., Ltd., model 0756), polyvinyl acetate emulsion (Tg value is about 42°C, brand Vinamul 8482) and polyvinyl acetate-ethylene emulsion (Tg value is 0°C, Dalian Chemical DA-179), with a weight ratio of 1:0.5:0.2; the filler is modified calcium carbonate, and the average particle diameter is 50nm; the leveling agent is BYK302; the adhesion promoter is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the defoamer is TEGO Airex901W, the bactericide is 1,2-benzisothiazolin-3-one, and the wetting and dispersing agent is paraffin;

[0063] The preparation method of the aerogel paste is as follows: based on the total weight of 100%, 15% of silica aerogel powder, 6% of active agent and the rest of water are mixed and then stirred and dispersed at 2000r / min; wherein the active agent is ethylene glycol monostearate and polyoxyethylene dioleate, and the weight ratio of the two is 1:1; the particle size of the aerogel powder is 500nm, the density is 0.1g / mL, and the specific surface area is 600m 2 / g, thermal conductivity is 0.04W / (m·k);

[0064] The preparation method of the modified calcium carbonate is as follows: calcium carbonate is placed in deionized water to form a 10wt% suspension, ultrasonically dispersed and then heated to 90°C, an ethanol solution containing 8wt% of γ-mercaptopropyltriethoxysilane (modifier) ​​is added while stirring, the mixture is stirred at a constant temperature for 4h, then filtered and dried to obtain the modified calcium carbonate.

[0065] The preparation method of the thermal insulation putty paste is the same as that of Example 1.

[0066] Example 3

[0067] The present embodiment provides an aerogel thermal insulation putty paste, and the raw materials for preparation include: by weight, 15 parts of emulsion, 40 parts of aerogel paste, 5 parts of filler, 0.1 parts of leveling agent, 0.1 parts of adhesion promoter, 0.1 parts of defoaming agent, 0.2 parts of bactericide, 0.1 parts of wetting dispersant, and 5 parts of water;

[0068] The emulsion is a combination of styrene acrylic emulsion (Tg value is 28°C, Shanghai Zhenzhou Chemical Coatings Co., Ltd. KB-68), polyvinyl acetate emulsion (Tg value is about 42°C, brand Vinamul 8482) and polyvinyl acetate-ethylene emulsion (Tg value is 0°C, Dalian Chemical DA-179), with a weight ratio of 1:1:1; the filler is modified calcium carbonate, and the average particle diameter is 200nm; the leveling agent is BYK302; the adhesion promoter is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, the defoamer is TEGO Airex 901W, the bactericide is 1,2-benzisothiazolin-3-one, and the wetting and dispersing agent is paraffin;

[0069] The preparation method of the aerogel paste is as follows: based on the total weight of 100%, 10% of silica aerogel powder, 0.5% of active agent and the balance of water are mixed and then stirred and dispersed at 1000r / min; wherein the active agent is ethylene glycol monostearate and polyoxyethylene dioleate, and the weight ratio of the two is 1:3; the particle size of the aerogel powder is 10nm, the density is 0.6g / mL, and the specific surface area is 1000m 2 / g, thermal conductivity is 0.01W / (m·k);

[0070] The preparation method of the modified calcium carbonate is as follows: calcium carbonate is placed in deionized water to form a 5wt% suspension, ultrasonically dispersed and then heated to 90°C, an ethanol solution containing 4wt% of γ-mercaptopropyltriethoxysilane (modifier) ​​is added while stirring, the mixture is stirred at a constant temperature for 1h, then filtered and dried to obtain the modified calcium carbonate.

[0071] The preparation method of the thermal insulation putty paste is the same as that of Example 1.

[0072] Example 4

[0073] The same as Example 1, except that: the styrene acrylic emulsion has a Tg value of 15°C and is purchased from Jiangsu Shengda New Materials Co., Ltd., model S-01.

[0074] Example 5

[0075] It is basically the same as Example 1, except that: the Tg value of the polyvinyl acetate-ethylene emulsion is -10°C, and it is purchased from Shandong Haochen New Material Technology Co., Ltd.

[0076] Example 6

[0077] The method is basically the same as Example 1, except that the weight ratio of the styrene acrylic emulsion, the polyvinyl acetate emulsion and the polyvinyl acetate-ethylene emulsion is 1.5:0.5:0.2.

[0078] Example 7

[0079] The method is basically the same as Example 1, except that in the preparation method of the modified calcium carbonate, the modifier is propyltriethoxysilane.

[0080] Example 8

[0081] The method is basically the same as Example 1, except that in the preparation method of the modified calcium carbonate, the mass concentration of γ-mercaptopropyltriethoxysilane (modifier) ​​in the ethanol solution is 12wt%.

[0082] Example 9

[0083] The method is basically the same as Example 1, except that the wetting and dispersing agent is sodium tripolyphosphate.

[0084] Example 10

[0085] The method is basically the same as Example 1, except that the adhesion promoter is 3-aminopropyltrimethoxysilane.

[0086] Comparative Example 1

[0087] The method is basically the same as Example 1, except that: the emulsion does not include polyvinyl acetate-ethylene emulsion, and the weight ratio of the used styrene acrylic emulsion and polyvinyl acetate emulsion is 1:0.7.

[0088] Comparative Example 2

[0089] The method is basically the same as Example 1, except that: the emulsion does not include polyvinyl acetate emulsion; the weight ratio of the used styrene acrylic emulsion and polyvinyl acetate-ethylene emulsion is 1:0.5.

[0090] Comparative Example 3

[0091] The method is basically the same as Example 1, except that no active agent is added to the aerogel paste.

[0092] Performance testing method:

[0093] 1. Tensile bond strength: According to the JG / T253-2011 test standard, the standard bond strength (cured at room temperature for 28 days) and the water immersion bond strength (cured at room temperature for 28 days, then immersed in water for 7 days) are tested;

[0094] 2. Thermal conductivity: According to GB / T10294-2008 test standard.

[0095] Performance test results:

[0096] The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] Test data analysis: The test results of Examples 1-3 show that the aerogel thermal insulation putty paste of the present application has excellent bonding strength, water resistance, and thermal insulation performance, and can be used in practical applications.

[0101] Comparison of Example 1 and Example 4-5: Only when the compounded emulsion has a suitable Tg value can the system be guaranteed to have a relatively high cohesive strength and dispersibility, and perfectly solve the problem of increased water absorption of putty paste caused by aerogel materials. The glass transition temperature of the styrene acrylic emulsion in Example 4 is too low, which means that the rigid structure of the benzene ring in its system is reduced. Although this helps to disperse the aerogel paste and other solid components in the system, it will lead to a decrease in the hydrophobicity of the material; the polyvinyl acetate-ethylene emulsion in Example 5 also has a too low Tg value. Although the polyvinyl acetate-ethylene emulsion can increase the soft segment in the system and better balance the rigidity and toughness of the putty-based material, when its Tg value is too low, the spatial activity of the material components is greater, and the cohesion of the system is excessively reduced, which will also affect the stability and strength of the material network structure, and the hydrophobic performance will decrease.

[0102] Comparison of Example 1 and Example 6: Controlling the relative content of the compounded emulsion can regulate the structure of the system. For styrene-acrylic emulsion, the benzene ring in its molecular chain not only improves the mechanical strength of the material, but also produces a large steric hindrance, and the dispersion uniformity of the solid component in the system is poor, resulting in differences in the hydrophobicity and thermal conductivity of the material.

[0103] Comparison of Example 1 and Example 7-8: The organic long chain of the modifier can increase the dispersibility and bonding properties of calcium carbonate in the system. It is grafted on the surface of calcium carbonate through silicon-oxygen bonds, and the organic chain segment at the other end participates in building the network structure of the material, so that calcium carbonate can be fixed therein. The thiol group at the other end produces intermolecular effects with the functional groups in the system or the wall base material, which not only improves the cohesion of the putty paste, but also enhances the bonding strength to the base; however, the modifier of Example 7 does not have polar groups and does not contribute to the cohesion and bonding strength. Similarly, when the modifier in Example 8 is added in excess, the intermolecular effect with the wall base material is enhanced, but the cohesion of the material increases and the fluidity decreases, and the polar bond adsorption of water increases, resulting in a decrease in the overall performance of the material.

[0104] Comparative Example 1 and Example 9: Paraffin wax not only has a wetting and dispersing effect, but is also beneficial to the thermal insulation performance of the putty paste. Although sodium polyphosphate can promote the dispersion of solid matter, it has a certain water absorption effect, which causes the putty paste to absorb more water and reduce the water-immersion bonding strength.

[0105] Comparative Example 1 and Example 10: When the putty paste is used, the silane adhesion promoter will be arranged on the surface of the substrate through silicon-oxygen bonds, while the organic chain segment at the other end is connected with other organic components by intermolecular forces, thereby promoting the adhesion of the putty paste to the substrate. However, the presence of a cyclic rigid structure in β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can enhance the structural strength of the putty paste and reduce its water absorption; while 3-aminopropyltrimethoxysilane contributes less to the hydrophobicity of the putty paste.

[0106] Comparative Example 1 and Comparative Example 1-2: Only when the three emulsions are compounded and used, their combined effect can make the network structure of the putty paste have suitable strength and relative activity, so that each component can be stably fixed therein and have good dispersion performance. Removing any one of the components will have an adverse effect.

[0107] Comparative Example 1 and Comparative Example 3: The active agent is beneficial to the dispersion of aerogel and maintains the stability of the internal microporous structure, thereby improving the density and thermal insulation performance of the putty paste; the hydroxyl groups on the surface of the active agent are combined with the hydroxyl groups on the surface of the aerogel powder. Compared with ethylene glycol monostearate, the arrangement of polar groups and double bonds in the structure of polyoxyethylene dioleate can better fix the aerogel in the system, while ethylene glycol stearate can better adjust the activity of the aerogel powder in the system and improve the dispersion effect.

Claims

1. An aerogel thermal insulation putty paste, characterized in that: The raw materials include: by weight, 13-50 parts of emulsion, 30-70 parts of aerogel paste, 5-30 parts of filler, 0.1-2 parts of leveling agent, 0.1-3 parts of adhesion promoter, 0.1-1 parts of defoamer, 0.1-1 parts of bactericide, 0.1-1 parts of wetting dispersant, and 5-20 parts of water; The emulsion includes styrene acrylic emulsion, polyvinyl acetate emulsion and polyvinyl acetate-ethylene emulsion; The weight ratio of the styrene acrylic emulsion, the polyvinyl acetate emulsion and the polyvinyl acetate-ethylene emulsion is 1: (0.5-1): (0.2-1); the Tg value of the styrene acrylic emulsion is 20-45°C, the Tg value of the polyvinyl acetate emulsion is 30-50°C; the Tg value of the polyvinyl acetate-ethylene emulsion is -5~10°C; the composition of the aerogel paste is: based on the total weight of 100%, 10-15% of aerogel powder, 0.5-6% of active agent, and the balance of water.

2. The thermal insulation putty paste according to claim 1, characterized in that: The active agent is ethylene glycol monostearate and polyoxyethylene dioleate, and the weight ratio of the two is 1: (1-3).

3. The thermal insulation putty paste according to claim 1, characterized in that: The filler comprises calcium carbonate and / or glass microbeads; the calcium carbonate is modified calcium carbonate; the modifier is at least one of vinyl triethoxysilane, 3-(methacryloyloxy)propyl trimethoxysilane, 3-aminopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane and γ-mercaptopropyl trimethoxysilane.

4. The thermal insulation putty paste according to claim 3, characterized in that: The modifier is γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane.

5. The thermal insulation putty paste according to claim 4, characterized in that: The adhesion promoter is β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.

6. The method for preparing the thermal insulation putty paste according to any one of claims 1 to 5, characterized in that: The method is: S1. Mix water, aerogel paste, filler, leveling agent, adhesion promoter, defoamer and wetting dispersant and stir at high speed; S2. Add the emulsion and the fungicide into S1 and mix and stir to obtain the thermal insulation putty paste.

Citation Information

Patent Citations

  • Preparation method of aerogel thermal-insulating coating

    CN103911030A

  • A building exterior wall insulation putty and its preparation method

    CN108529990B

  • Heat insulation putty and preparation method thereof

    CN105295496A